Effets d`un exercice de type anaérobie sur le statut antioxydant enzymatique au cours de la récupération chez les judokas - Abed, K. E.; Trabelsi, K.; Latiri, I.; Hakim, A.; Tabka, Z.; Zbidi, A. (Science & Sports, 2009)
Aim To evaluate the effect of the anaerobic exercise on the enzymatic antioxidant statute in judokas` regional level, because the effects of anaerobic exercise on the free radicals and antioxidants are relatively rare and have some divergences.